أثر التحفظ المحاسبي المشروط في ملاءمة قيمة الأرباح المحاسبية والقيمة الدفترية للسهم في سوق أبوظبي للأوراق المالية (دراسة على الشركات الخدمية) - الطويل ليلى; شاهين سوسن (Latakia University Journal - Economic and Legal Sciences Series, 2018)
تختبر هذه الدراسة تأثير التحفظ المحاسبي المشروط في ملاءمة قيمة الأرباح المحاسبية والقيمة الدفترية للسهم للشركات الخدمية المدرجة في سوق أبوظبي للأوراق المالية، وقد تم اختيار سوق أبو ظبي لعدم توفر البيانات اللازمة في سوق دمشق للأوراق المالية. اعتمدت هذه الدراسة على نموذج Basu(1997) لقياس مستوى التحفظ المحاسبي، وعلى نموذج السعر المطور في أدبيات ملاءمة القيمة، وذلك باستخدام بيانات القوائم المالية الربعية والسنوية خلال الفترة الممتدة من عام 2006 إلى عام 2014.بينت نتائج الدارسة زيادة في ملاءمة قيمة الأرباح المحاسبية والقيم الدفترية للأسهم في الشركات التي تطبق التحفظ المحاسبي، بالمقابل أظهرت النتائج انخفاض ملاءمة قيمة الأرباح المحاسبية بشكل كبير في الشركات التي لا تطبق التحفظ المحاسبي وعدم ملاءمة القيم الدفترية لهذه الشركات.تدل هذه النتائج على أهمية التحفظ المحاسبي في زيادة ملاءمة قيمة المعلومات المحاسبية ممايتعارض مع استبعاد التحفظ من الإطار المفاهيمي كخاصية غير مرغوبة. This study examines the effect of conditional accounting conservatism on the value relevance of accounting earnings and book value per share for listed service firms in Abu Dhabi Securities Exchange. Abu Dhabi Securities Exchange was selected due to the unavailability of data in Damascus Securities Exchange. This paper is based on Basu model (1997) to measure the level of conservatism, and on the price model which is developed in value relevance literature.Data was collected using the annual and quarterlyfinancial statements for the period 2006 to 2014. Results of this research showed increased value relevance of accounting earnings and book values for firms that apply accounting conservatism. In contrast, these results showed decreased value relevance of accounting earnings for firms that don’t apply accounting conservatism, and also the book values for these firms are not relevant. It can be concluded that accounting conservatism playsimportant rolein increasing the value relevance of accounting information, which apparentlycontradict with removingconservatism from the accounting conceptual framework as undesirable characteristic.